2021
DOI: 10.1021/acs.jafc.1c01898
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharides from Lactobacillus plantarum NCU116 Facilitate Intestinal Homeostasis by Modulating Intestinal Epithelial Regeneration and Microbiota

Abstract: Regeneration of epithelia is crucial for maintaining the intestinal barrier and homeostasis. Our previous work showed that exopolysaccharides from Lactobacillus plantarum NCU116 (EPS116) regulated the barrier function and homeostasis of the intestine; however, the relevant mechanisms remain obscure. Therefore, we sought to explore the role of EPS116 in promoting intestinal epithelial regeneration. Our data showed that the administration of EPS116 markedly ameliorated inflammatory bowel disease-related phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 44 publications
3
39
0
2
Order By: Relevance
“…In addition, DSS-induced pathological damage in the colon was also improved after EPS-1 administration. Similar effects were also found in the previous results [14,17]. Therefore, EPS-1 administration showed a good preventive effect on the DSS-induced UC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, DSS-induced pathological damage in the colon was also improved after EPS-1 administration. Similar effects were also found in the previous results [14,17]. Therefore, EPS-1 administration showed a good preventive effect on the DSS-induced UC.…”
Section: Discussionsupporting
confidence: 91%
“…longum YS108R could protect against the development of UC by maintenance of the mucosal barrier and gut microbiota modulation [15]. The EPS produced by L. plantarum NCU116 could regulate the barrier function, modulate the gut microbiota structure, and elevate c-Jun/Muc2 signaling pathway in an UC mouse model induced by DSS [16,17]. Compared to the traditional drugs, LAB-produced EPS would likely possess beneficial effects and further avoid the severe side effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria have gained substantial attention in maintaining intestinal homeostasis [ 26 ]. For a new probiotic strain, stable adhesion to the intestinal epithelium is one of the crucial criteria for evaluating probiotic action, which contributes to the competition between probiotics and pathogenic bacteria for the adhesion to intestinal epithelium [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that Staphylococcaceae was consistently augmented in IBD and colon cancer [ 2 , 23 ]. Zhou et al reported that exopolysaccharides produced by Lactiplantibacillus plantarum NCU116 significantly decreased the relative abundance of Staphylococcaceae in the fecal of DSS-induced C57BL/6 mice [ 41 ]. Our results suggested that oral LPEPS were beneficial to maintain the gut microbiota balance and promote intestinal health of the C57BL/6 mice treated by AOM/DSS.…”
Section: Discussionmentioning
confidence: 99%